HUBUNGAN PERAN LINGKUNGAN SEKOLAH DENGAN KESIAPAN BEKERJA SISWA TEKNIK OTOMOTIF - Dianastiti, Yelma; Andhika Putra, Rico (Jurnal Pendidikan Vokasi Otomotif, 2025)
Abstract The work readiness of Vocational High School graduates remains a major challenge in vocational education, mainly due to the suboptimal role of the school environment in supporting the development of students’ technical and non-technical competencies. This study focuses on analyzing the relationship between the role of the school environment and students’ work readiness at SMKN 2 Tulungagung. A mixed methods approach with a convergent parallel design was applied, in which quantitative and qualitative data were collected simultaneously, analyzed separately, and then integrated. The sample consisted of 140 students of the Motorcycle Engineering program who had completed industrial work practice, along with in-depth interviews with eight students. Regression analysis showed a positive and significant relationship between the school environment and work readiness, with a correlation coefficient of 0.612 and a determination value of 0.375. Qualitative findings reinforced this result, highlighting that peer support, adequate facilities, a conducive learning atmosphere, and effective time management contribute to improving students’ technical skills, discipline, and confidence. It can be concluded that a supportive school environment—physically, socially, and psychologically plays an essential role in shaping Vocational High School students’ readiness to enter the industrial world. Keywords: School environment, work readiness, vocational education, Vocational High School, mixed methods Abstrak Kesiapan bekerja lulusan Sekolah Menengah Kejuruan masih menjadi tantangan utama dalam pendidikan vokasi, terutama karena belum optimalnya peran lingkungan sekolah dalam mendukung pembentukan kompetensi teknis dan nonteknis siswa. Penelitian ini berfokus pada analisis hubungan antara peran lingkungan sekolah dengan kesiapan bekerja siswa SMK Negeri 2 Tulungagung. Penelitian menggunakan pendekatan mixed methods dengan desain convergent parallel, di mana data kuantitatif dan kualitatif dikumpulkan secara bersamaan, dianalisis secara terpisah, lalu diintegrasikan. Sampel terdiri dari 140 siswa kelas XI dan XII program keahlian Teknik Sepeda Motor yang telah mengikuti Praktik Kerja Lapangan, disertai wawancara mendalam terhadap delapan siswa. Hasil analisis regresi menunjukkan adanya hubungan positif dan signifikan antara peran lingkungan sekolah dan kesiapan bekerja, dengan nilai koefisien korelasi sebesar 0,612 dan determinasi 0,375. Data kualitatif memperkuat hasil tersebut dengan menegaskan bahwa dukungan teman sebaya, fasilitas memadai, suasana belajar kondusif, dan pengaturan waktu efektif berkontribusi terhadap peningkatan keterampilan, disiplin, dan kepercayaan diri siswa. Disimpulkan bahwa lingkungan sekolah yang mendukung secara fisik, sosial, dan psikologis berperan penting dalam membentuk kesiapan kerja siswa SMK menghadapi dunia industri. Kata Kunci: Lingkungan sekolah, kesiapan bekerja, Sekolah Menengah Kejuruan, pendidikan vokasi, mixed methods